ТРАНСФОРМАЦІЯ ВИДАТКІВ МІСЦЕВИХ БЮДЖЕТІВ У КОНТЕКСТІ БЮДЖЕТНОЇ ДЕЦЕНТРАЛІЗАЦІЇ - Лободіна, Зоряна Миколаївна (Науковий журнал «Світ фінансів», 2017)
Лободіна З. М. Трансформація видатків місцевих бюджетів у контексті бюджетної децентралізації. Узагальнено наукові підходи до трактування дефініцій “видатки бюджету” та “видатки місцевих бюджетів”, що дало можливість розкрити складну економічну природу видатків місцевих бюджетів, обґрунтувати їх роль у забезпеченні виконання повноважень органів місцевого самоврядування. Проаналізовано вплив видатків місцевих бюджетів як важеля механізму реалізації бюджетної політики на соціально-економічний розвиток адміністративних територій. Виявлено проблеми трансформації видатків місцевих бюджетів в контексті бюджетної децентралізації, обґрунтовано необхідність та шляхи їх вирішення. Лободина З. М. Трансформация расходов местных бюджетов в контексте бюджетной децентрализации. Обобщены научные подходы к трактовке дефиниций “расходы бюджета” и “расходы местных бюджетов”, что позволило раскрыть сложную экономическую природу расходов местных бюджетов, обосновать их роль в обеспечении исполнения полномочий органов местного самоуправления. Проанализировано влияние расходов местных бюджетов как рычага механизма реализации бюджетной политики на социально-экономическое развитие административных территорий. Определены проблемы трансформации расходов местных бюджетов в контексте бюджетной децентрализации, обоснована необходимость и пути их решения. Lobodina Z. Transformation of expenditures of local budgets in the context of budget decentralization. With falling of economic growth rate in Ukraine important role in the exercise of powers of local self-governments and meeting the needs of local communities in social services is given to local budgets. At the present Ukrainian society is colliding with many challenges of the execution of expenditures of local budgets. They negatively influence on the opportunities to ensure constitutional rights of Ukrainian citizens. These circumstances determine the relevance of research of transformation of expenditures of local budgets and evaluation of their role in the implementation of budget policy at the local level. It is, in spite of permanent reform of budget relations, focused mainly on support the regions, and not on their development. The purpose is the scientific substantiation of conceptual foundations of expenditures of local budgets as a lever of implementation of budget policy, monitoring their realization and transformation in the context of fiscal decentralization. Scientific approaches to the interpretation of the definitions of “expenditures of budget” and “expenditures of local budgets” are summarized. This made it possible to reveal the difficult economic nature of expenditures of local budgets, to justify their role in ensuring of exercise of powers of local self-governments. The impact of expenditures of local budgets as a lever mechanism for implementing budge policy on economic and social development of administrative areas is analyzed. The expenditures of local budgets is multidimensional and complex economic phenomena. The role of local spending is manifested in the fact that they are a lever mechanism of realization of budget policy at the local level, refl ect its priorities, the degree of budget decentralization and directly proportional influence on the gross regional product. During the research author has found the problems of transformation of local budgets expenditures in the context of budget decentralization and has grounded solutions.